Analysis Of Iron (Fe) In Papaya Fruit (Carica Papaya L.) - Ifa Nurhasanah (Sean Institute, 2023)
Papaya fruit contains several nutrients in it. One of the Hawaiian types that has nutritional content to increase a person's Hb level is iron. The purpose of this study was to determine and analyze iron levels in Hawaiian papayas. The method used in this study was to use an Atomic Absorption Spectrophotometer (AAS) which was carried out at the Sucofindo Surabaya laboratory in September 2022-January 2023. The results of this study indicated that there is an iron content in the Hawaiian papaya fruit. The results of the analysis of iron levels in this fruit which was carried out at 10-20 grams were 5.1. In conclusion, the existence of Hawaiian papaya fruit can help people to meet their daily iron needs, so that they can increase Hb